Penggunaan Metode Saintifik Pada Pembelajaran PAI Terhadap Anak Tunagrahita di SLB Rela Bhakti II Wates - Janingsih, Janingsih; Amarilis R.M. , Bunga; Luthfi N , Muhammad; Husna , Difa’ul (Jurnal Multidisiplin Indonesia, 2023)
The aim of this research is to describe the use of scientific methods in PAI learning for mentally retarded children, analyzing the results achieved at SLB Rela Bhakti II Wates. This research is a qualitative descriptive study involving people and collecting data related to the learning model and the impact of using this method. The research location is SLB Rela Bhakti II Wates. This data was collected by observing schools, interviews with teachers, and taking documentation. Analysis of the data uses presentation of the data and drawing conclusions from it. The results of the research at this SLB school are learning in PAI subjects which focuses on applied learning methods, habits with religious values ​​such as reading Iqra' and providing broad knowledge. The results achieved in learning PAI related to independent religion vary depending on the child's ability to understand.